English centre vs. Celtic periphery: the Chief Rabbi, Shechita and Dundee, 1883. Issue 2 (4th May 2018) - Abrams, Nathan
ABSTRACT: Using a case study from Dundee, this article scrutinises historians' assumptions about the nature of links between the major British-Jewish centres and 'the periphery'. Utilising a cache of letters addressed to the Chief Rabbi concerning the provision of a trained Jewish butcher ( shochet ) in 1883, Abrams considers the Jewish community of Dundee in northeast Scotland as an example of Jews at a temporal, organisational, cultural and geographical frontier. The episode to which these letters refer tests the assumption of Anglo-Jewish historians that the provincial communities were considered, and considered themselves, subordinate to the regularly constituted ecclesiastical authorities in London.